STUDIES ON THE MORTALITY OF SPAWN AND FRY OF INDIAN MAJOR CARPS DURING TRANSPORT Part III. Effect of Inimical Substances from Decomposition of metabolic products in the medium on Spawn Life and their control - Saha, K C; Sen, D P; Mazumdar, P (Indian Journal of Fisheries, 2015)
It has been reported in a separate communication (Saha etal, 1956) that maintenance of dissolved oxygen balance in a medium for transport of spawn and fry is an important condition on which the success of transport largely depends. It has also been indicated therein that, in a closed system under oxygen balance, a portion of the dissolved oxygen is utilised for oxidation of metabolic products of the fish-seeds and for metabolism of bacteria present in the medium, as a result of which the system becomes gradually unbalanced, affecting the seed-life. In addition, inimical gases like carbon dioxide and ammonia, resulting from metabolic products and decomposition of dead seeds and bacterial cells, beyond certain concentration, adversely affect the physiological condition of the fish-seeds, causing mortality. Such conditions may arise even when the system is balanced with respect to dissolved oxygen, but the time lag depending on the factors like pressure of oxygen, concentration of seeds in the medium, volume of water, etc.